Distribution Characteristics of the Plasma Irregularities Inside the Mid‐Latitude Ionospheric Trough Based on Swarm In Situ Measurements - Yiwen Liu; Wenhao Xie; Chao Xiong; Ting Ye; Yuhao Wang; Xin Wan; Yueyan Cao (Space Weather)
Abstract A large number of studies have confirmed the frequent occurrence of mid‐latitude trough irregularities (MTI), but the distribution characteristics of these irregularities are still pending. Based on the Swarm in situ plasma measurements from 2014 to 2020, the dependences of MTI on magnetic local time, season, solar flux, and geomagnetic activities are analyzed. The results show that for the irregularities with scale‐size of about 7.5–75 km. (a) Geomagnetic activity has an obvious inhibitory effect on the formation of MTI, regardless on the dayside or nightside. (b) The daytime MTI occurrence rate is significantly higher than that at nighttime, and the difference between the poleward wall and equatorward wall during daytime is higher than that at nighttime. (c) The dayside MTI occurrence rate appears highest in winter and lowest in summer, but the nightside MTI occurrence rate appears highest in equinoxes and lowest in winter. (d) The nightside MTI show lower occurrence rate under high solar activity conditions, but no obvious solar activity influence is shown on the dayside. It is suggested that the temperature gradient instability plays an important role in causing the seasonal effect of the nightside MTI, but cannot directly support the solar activity effect. The relatively low nightside MTI occurrence rate in high solar activity years probably results from the relatively small electron temperature gradient. It is speculated that the formation of nightside MTI not only requires the antiparallel conditions of density gradient and temperature gradient, but may also needs to meet the enough large magnitude of the two gradients.